PEMAHAMAN KELUARGA TENTANG KONDISI FISIK RUMAH DAN IDENTIFIKASI RISIKO INFEKSI SALURAN PERNAFASAN AKUT (ISPA) PADA BALITA - Fathimi Fathimi; Hilma Yasni; Asmanidar Asmanidar (Poltekkes Kemenkes Aceh, 2022)
Acute Respiratory Infection (ARI) often occurs in toddlers, generally limited to the top but about 5% of the bottom. Overall efforts to reduce maternal and child mortality have slowed, even reaching a point of stagnation over the last 5-10 years (Cissy, 2010). The high infant mortality rate in developing countries is related to the high level of air pollution. Is the impact of environmental risks such as indoor and outdoor air pollution. A polluted environment is very dangerous for toddlers because developing organs and immune systems, respiratory tracts and smaller bodies make toddlers more vulnerable to dirty air and water. Aceh Province ranks 10th out of 34 other provinces with an ARI rate of 10%, still far from the national maximum achievement, the ARI rate in Indonesia is only 9.3% (Riskesdas, 2018). Objective: To determine the relationship family understanding of the physical condition of the house and the ability to identify ARI risks. Methods: Observational research with a cross sectional study design, carried out on families with toddlers on December 3-4, 2020, the sampling technique is non-probability sampling by means of quota sampling, the number of samples studied is 42 families. Results: Bivariate analysis showed that there was a relationship family understanding and the ability to identify ARI risk (P=0.005), multivariate analysis showed that family understanding of residential density had a higher influence (P=0.005). OR=2.89). Conclusions and Suggestions: There is a need to improve the quality of family human resources, there is a need for cross-sectoral and cross-program collaboration.